Bone grafting in implantology - A critical review (Research, Society and Development, 2024)
Introduction: The use of bone grafts in implant dentistry is a consolidated and essential practice for the reconstruction of bone defects and the adequate preparation of the bone bed for the installation of dental implants. Objective: to describe the advances, challenges, and solutions in using bone grafts in implant dentistry. Methodology: In this literature review, a search was done in the digital database of scientific articles available at PubMed, SciELO, Google Scholar, and Periodicals Capes. Results and Discussion: The use of bone grafts in implant dentistry has played a crucial role in the reconstruction of bone defects and the adequate preparation of the bone bed for the installation of dental implants. This technique is widely used in patients with bone loss due to various factors, including periodontal disease, trauma, and bone resorption following tooth extractions. Conclusion: Despite significant advances in the field, challenges remain, such as the morbidity associated with obtaining autogenous grafts and the possibility of graft resorption. Continued studies in oral health are essential to improve the techniques and materials available further. disharmonies of the anterior teeth due to alterations in color, shape, texture, and size influence the smile and are common aesthetic complaints.